Proper name anomia with preserved lexical and semantic knowledge after left anterior temporal lesion: A two-way convergence defect. (April 2015) - Busigny, Thomas; de Boissezon, Xavier; Puel, Michèle; Nespoulous, Jean-Luc; Barbeau, Emmanuel J.
Abstract: This article describes the case of a patient who, following herpes simplex encephalitis (HSE), retained the ability to access rich conceptual semantic information for familiar people whom he was no longer able to name. Moreover, this patient presented the very rare combination of name production and name comprehension deficits for different categories of proper names (persons and acronyms). Indeed, besides his difficulty to retrieve proper names, SL presented a severe deficit in understanding and identifying them. However, he was still able to recognize proper names on familiarity decision, demonstrating that name forms themselves were intact. We interpret SL's deficit as a rare form of two-way lexico-semantic disconnection, in which intact lexical knowledge is disconnected from semantic knowledge and face units. We suggest that this disconnection reflects the role of the left anterior temporal lobe in binding together different types of knowledge and supports the classical convergence-zones framework (e.g., Damasio, 1989) rather than the amodal semantic hub theory (e.g., Patterson, Nestor, & Rogers, 2007).